HUBUNGAN KUALITAS PELAYANAN DENGAN REKOMENDASI MAHASISWA - Euis Winarti (JURNAL LENTERA BISNIS, 2012)
The Relationship between Service Quality with the Student's Recommendation.The benefit of this research is expected, to become  the guidance for the managerial, mainly in upgrading the service quality in term of upgrading the student's recommendation.The purpose of this research is to examine the hypothesis of relationship between Service Quality with Student's Recommendation. In drawing the sample used "Pusposive Sampling" technique, in data analysis is used a statistic descriptive and in hypothesis correlation technique.The result of all research variables (service quality, and student's recommendation) shows average (good enough) by the student. All the hypothesis are accepted because the P Value < 0.05, it means that Ho is unaccepted and HA is accepted: So that there is strong relationship between service quality with the student's recommendation. All the hypothesis in its variable has relationship which is stated in coefficient correlation (r). Marked r all positive (+) which means leads to one-way relationship between service quality with student's recommendation. The service quality variable has the strong relationship with student's recommendation